Comparison of efficacy and safety of intravenous iron sucrose and intramuscular iron sorbitol therapy in patients with anemia during pregnancy in a developing country - Gaikwad, Harsha Shailesh; Sindhu, Anu; Sarda, Nivedita (Asian Journal of Medical Sciences, 2017)
Background: Iron deficiency anemia due to poor nutritionis estimated to affect nearly two thirds ofall pregnant women in developing countriesparticularly in India. The responsible constellation of factors producing iron deficiency anemia generally precede the pregnancy, which includedeficient diet in iron content coupled with menstrual losses,generally a rapid succession of pregnancies and inadequate supplemental iron are a few to be blamed for a high incidence of anemia in such population. Aims and Objectives: To compare the efficacy and safety of iron sucrose versus iron sorbitol therapy in pregnant anemic patients. Material and Methods: Two-hundred antenatal women attending the out patient department having hemoglobin levels of 8 gm% or less were recruited in the study and were randomized into two groups for receiving intravenous and intramuscular iron therapy. Results and Conclusions: There was a significant improvement in the haematologicalparameters and no major side effects developed in the intravenous iron sucrose group.Though there was a significant improvement in the haematological parameters after intramuscular iron sorbitol therapy also butnone of the cases reached the target level of haemoglobinduring the observation period. Asian Journal of Medical Sciences Vol.8(5) 2017 31-35